Rethinking Connectivity as Recontextualisation : Issues for Research and Practice - Guile, David [Verfasser] (My University, 2020)
"This contribution explains why, once a number of issues which were an explicit and implicit feature of the connective typology of work experience (GRIFFITHS/GUILE, 2004) are conceptualised as the recontextualisation of knowledge, it becomes possible to see that boundary crossing is a ubiquitous feature of vocational and professional education, rather than an issue of learners crossing the boundary between education and work. The contribution tackles this goal in the following way. Firstly, it offers a brief explanation of the development of the connective typology of work experience. Next, it explains why the notion of 'resitation' in the connective typology of work experience was an early, but circumscribed, attempt to articulate the concept of recontextualisation. lt then explains the origins and development of the concept of recontextualisation and that this concept offers a unified perspective on initial and continuing vocational formation. Tue contribution concludes by identifying a) the practical implication of the concept of recontextualisation for capacity / competence development and b) the future research challenge for VET, especially in relation in the emergence of 4th generation technologies." (author's abstract; BIBB-Doku)

"Dieser Beitrag legt dar, warum es möglich wird, Grenzüberschreitungen als ein allgegenwärtiges Merkmal der beruflichen Aus- und Weiterbildung zu sehen - und nicht als ein Problem von Lernenden, die die Grenze zwischen Bildung und Arbeit überschreiten - sobald einige explizite und implizite Merkmal der konnektiven Typologie der beruflichen Erfahrung (GRIFFITHS/ GUILE, 2004) als Rekontextualisierung von Wissen konzipiert werden. Der Beitrag geht dieses Ziel wie folgt an: Als erstes wird eine kurze Erklärung für die Entwicklung der konnektiven Typologie der beruflichen Erfahrung gegeben. Als nächstes wird erklärt, warum der Begriff der "Resitation" in der konnektiven Typologie der Berufserfahrung ein früher, aber begrenzter Versuch war, den Begriff der Rekontextualisierung zu artikulieren. Dann werden die Ursprünge und die Entwicklung des Konzepts der Rekontextualisierung erörtert sowie die Idee, dass dieses Konzept eine einheitliche Perspektive auf die berufliche Aus- und Weiterbildung bietet. Der Beitrag schließt mit der Identifizierung a) der praktischen Bedeutung des Konzepts der Rekontextualisierung für die Kompetenzentwicklung und b) der künftigen Herausforderungen für die Berufsbildungsforschung, insbesondere im Zusammenhang mit der Entstehung von Technologien der vierten Generation." (Autorenreferat; BIBB-Doku)
Keywords: L 2.1 Lernformen; Lernen und Arbeiten; Lernen am Arbeitsplatz; Situiertes Lernen